Refractory recurrent ocular graft versus host disease. Issue 12 (15th December 2019) - Greenan, Emily; Vandenberghe, Elisabeth; Murphy, Conor C
Abstract : Ocular graft-versus-host disease (GVHD) is one of the most frequent and long-term complications affecting patients after haematopoietic stem cell transplantation. It is associated with significant morbidity and a marked reduction in quality of life. Although common, currently there are no widely accepted guidelines available for its management, and no suggested regime of treatment that is completely satisfactory. So far, prophylactic treatment strategies for ocular GVHD have yet to be developed and treatment is normally initiated based on symptoms often after permanent ocular tissue changes and surface damage has occurred. Here we describe a case of recurrent ocular GVHD and its associated complications that was highly refractory to treatment.